2020
DOI: 10.1093/ijnp/pyaa061
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of White Matter Structural Networks in Chronic Schizophrenia Treated With Clozapine or Risperidone and Those Never Treated

Abstract: Background Despite its benefits, a major concern regarding antipsychotic treatment is its possible impact on the brain’s structure and function. This study sought to explore the characteristics of white matter structural networks in chronic never treated schizophrenia and those treated with clozapine or risperidone, and its potential association with cognitive function. Methods Diffusion tensor imaging was performed on a uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 66 publications
1
13
0
1
Order By: Relevance
“…The current findings, together with findings from previous studies, suggest that chronic exposure to antipsychotics may have an impact on anatomical organization of the CC in schizophrenia [ 11 , 12 ]. In this study, both CT-SCZ and RT-SCZ showed significantly increased FA values in the anterior CC region in comparison with NT-SCZ.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The current findings, together with findings from previous studies, suggest that chronic exposure to antipsychotics may have an impact on anatomical organization of the CC in schizophrenia [ 11 , 12 ]. In this study, both CT-SCZ and RT-SCZ showed significantly increased FA values in the anterior CC region in comparison with NT-SCZ.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, clozapine has a low affinity to dopamine D2 receptors [ 10 ]. In addition, our previous study on chronic schizophrenia showed less alterations in white matter structural networks in risperidone-treated patients compared with clozapine-treated or never-treated patients [ 11 ]. However, few studies have explored the effects of long-term monotherapy with clozapine or risperidone on callosal structure in chronic schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, clozapine has a low a nity to dopamine D2 receptors [10]. In addition, our previous study on chronic schizophrenia showed less alterations in white matter structural networks in risperidone-treated patients compared with clozapine-treated or never-treated patients [11]. However, few studies have explored the effects of long-term monotherapy with clozapine or risperidone on callosal structure in chronic schizophrenia.…”
Section: Introductionmentioning
confidence: 94%
“…In groups of never-treated and mono-antipsychotic treated chronic schizophrenia patients, FreeSurfer was used to automatically identify and segment CC for each participant to reduce random errors, rater errors and inter-participant variability of manual editing [12]. According to our previous ndings [11,[13][14][15], we hypothesized that long-term clozapine-treated (CT-SCZ) and risperidone-treated schizophrenia patients (RT-SCZ) would show different alterations in the volume and/or FA values of the CC.…”
Section: Introductionmentioning
confidence: 99%